2016
DOI: 10.1111/jace.14089
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Processing of Graphene/Leucite Nanocomposite Through Graphene Oxide/Geopolymer

Abstract: Graphene/leucite nanocomposites (rGO/leucite) were prepared through in situ reduction of graphene oxide/geopolymer (rGO/ KGP) composites. The effects of rGO on the microstructure and mechanical properties with respect to the geopolymer matrix after the high-temperature treatment were investigated systematically. The results show that GO is first partially reduced in the geopolymeric solution and then completely under the post high-temperature treatment. The rGO sheets undergo no interfacial reactions with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 38 publications
(65 reference statements)
2
16
0
Order By: Relevance
“…Meanwhile, the presence of rGO contributed to the enhancement of mechanical performance of geopolymer. As reported in our previous studies, 23,24 compared with pure geopolymer, improvements in mechanical properties were achieved through rGO reinforcement of 0.05-1 wt% at room temperature. With 1 wt% GO addition, the fracture toughness and exural strength of rGO/geopolymer composites increased by approximately 30% and 7%, respectively, attributing to the proper interface bonding, crack deection and propagation and rGO pull-out.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Meanwhile, the presence of rGO contributed to the enhancement of mechanical performance of geopolymer. As reported in our previous studies, 23,24 compared with pure geopolymer, improvements in mechanical properties were achieved through rGO reinforcement of 0.05-1 wt% at room temperature. With 1 wt% GO addition, the fracture toughness and exural strength of rGO/geopolymer composites increased by approximately 30% and 7%, respectively, attributing to the proper interface bonding, crack deection and propagation and rGO pull-out.…”
Section: Resultssupporting
confidence: 60%
“…[15][16][17] As a new nano ller material, it provided considerable potential in the fabrication of multifunctional polymers and ceramic matrix composites. [18][19][20] In our previous works, 9,12,13,[21][22][23][24][25] we have investigated Al 2 O 3 , 9 cenospheres, 21 carbon bers 12,13 and graphene oxide (GO) [22][23][24][25] reinforced geopolymer composites. However, the effects of graphene oxide addition on the geopolymerization mechanism of the rGO/geopolymer (rGO/KGP) during the processing was also not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…44 The pure KGP presents an exotherm peak at 1020°C and the weight loss is ~15 wt.%, which is attributed to the crystallization of leucite. 36 As for TG curve of the FHCs/KGP foams, weight loss of the FHCs/KGP foams is 11.17 wt.%. The DTA curve of H2 sample shows a peak centered at 300°C, which may be mainly caused by organic decomposition in the foams.…”
Section: Thermal Evolutionmentioning
confidence: 96%
“…Such mechanical improvement is also reported for graphene/leucite composites. 36 Kovářík et al 37 found that geopolymer foams transformed into leucite-based ceramic foams with open cell when sintering at 1300°C. Thus, it is worthy studying high-temperature performance of geopolymer foams to evaluate its thermal stability.…”
mentioning
confidence: 99%
“…Particularly, reduced graphene oxide (rGO) is used in construction for its large specific surface area, favorable mechanical strength, and high toughness [44][45][46][47]. In addition to this superior performance, rGO can effectively disperse in the highly alkaline environment of AAMs matrix (pH~12.5) due to electrostatic stabilization and significantly improve its mechanical properties [48][49][50].…”
Section: Introductionmentioning
confidence: 99%